P PERAN GURU RUPAKA DALAM PENDIDIKAN KARAKTER ANAK PADA MASA PANDEMI COVID-19 : PERAN GURU RUPAKA DALAM PENDIDIKAN KARAKTER ANAK PADA MASA PANDEMI COVID-19 - I Nyoman Alit Putra Merta (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Character education is an effort to create a generation of intelligent and noble character, with the Covid-19 pandemic, character education is more emphasized on the role of visual teachers to carry out character education. The problems discussed in this research are: 1) what is the role of visual teachers in children's character education during the covid-19 pandemic, 2) obstacles faced by visual teachers in children's character education during the covid-19 pandemic, and 3) how are the efforts of visual teachers in in character education for children during the Covid-19 pandemic. Types of qualitative research with data collection methods used to obtain data in this study are direct non-participant observation, unstructured direct interviews, and documentation. The informant determination technique used is purposive sampling, then the data obtained is processed through the steps of Data Reduction (data reduction), Data Display (data presentation), Conclusion (verification), from the analysis carried out in this study the results obtained: The role of visual teachers In character education for children during the Covid-19 pandemic, there are (1) the role of the visual teacher as an educator, (2) the role of the visual teacher as a role model, (3) the role of the visual teacher as a friend, and (4) the role of the visual teacher as a supervisor. The obstacles faced by visual teachers in children's character education during the Covid-19 pandemic were, (1) internal constraints, namely the character and innate nature of children, (2) external constraints, namely the lack of ability of visual teachers in managing character education and the influence of technological advances. Meanwhile, the efforts made by visual teachers in overcoming the obstacles encountered in children's character education during the Covid-19 pandemic were by giving more attention to children and controlling the use of technology by children. Keywords: Guru Rupaka, Character Education